SOSIALISASI MENINGKATKAN SUMBER DAYA MANUSIA DALAM MEWUJUDKAN JIWA ENTERPRENEURIAL - Ardiansyah, Rafli; Warjo, Amin; Sobirin (CV SWA Anugerah, 2024)
The entrepreneurial spirit is not only concerned with the ability to create new businesses, but also involves creative thinking skills, quick decision-making, and the ability to manage risks. Therefore, entrepreneurship-based human resource development requires a holistic approach involving skills training, mental training to encourage entrepreneurship, and training to manage existing resources. This activity is designed to equip participants with insights on business strategy, human resource development, financial management, and customer communication skills. With a better understanding, it is hoped that the civitas will be able to build a strong business foundation, manage risks, and create products and services that suit market needs.One of the strategic steps to increase economic independence and improve the country's competitiveness is to instill an entrepreneurial spirit in human resources. Bold and creative entrepreneurs are considered to have the ability to create new jobs and drive the country's economy. However, creating human resources with an entrepreneurial spirit is not an easy task. Effective and integrated strategies are needed, both through formal education, skills-based training, and strengthening the entrepreneurial ecosystem. Keywords: enterpreneurial, increase, human, resource,soul,and approach.